National Identity and Cultural Resilience in the Age of Globalisation - Iwanda Yogi Saputra; Zufar Rafidain Mujadi; Mochammad Bahrul Kurniawan (International Journal of Religion and Social Community, 2026)
This study aims to analyse the impact of globalisation on national identity and cultural resilience, and to formulate strategies for strengthening national values through the lens of Anthony Giddens’ Theory of Structuration. The study employs a qualitative descriptive approach using a literature review method. Data were obtained from various sources discussing globalisation, national identity, cultural resilience, and reflexive modernity, and were subsequently analysed interpretatively using Giddens’ concept of structural duality. The results of the study indicate that globalisation drives the transformation of values, behavioural patterns, and symbols of national identity through the penetration of global popular culture. This situation gives rise to a tendency towards individualism, changes in cultural consumption patterns, and a weakening of the internalisation of national values among some members of the younger generation. However, society is not passive; rather, it possesses the capacity to act as an agent capable of reproducing and transforming cultural values in line with evolving social contexts. Strategies to strengthen national identity and cultural resilience can be implemented through the process of disembedding and re-embedding national values within education, digital technology, popular culture, and the reinforcement of the Pancasila ideology. The novelty of this research lies in the use of Structuration Theory as a framework to explain the dynamic adaptation and reproduction of national values in the era of globalisation.